RANCANG BANGUN ALAT PENJERNIH AIR - Denny Jeremias Nusawakan; Wahida Wahida (Faculty of Agriculture, Musamus University, 2022)
Water is a natural resource that is very important for human life and other living things. Some of the water sources in the Merauke district come from a well or a swamp. The water is generally blackish brown in colour, has a smell, and has taste. This study aimed to design a water purification device. The method used in this study consisted of the preparation stage and water purifier design. The second stage was the construction of the water purification device, and the last stage was the trial of the tool. The materials used in this study were: alum, gravel, palm fibre, sand, charcoal, large-size gravel, gauze, swamp water, water from a well, and faucets. The tools used are a gallon water dispenser and a gallon water dispenser holder. The filter tool consisted of 2-gallon water dispensers. The filter material consisted of palm fibre, charcoal, sand and large gravel. In the pre-trial process using swamp water (blackish brown) and well water (brown), the volume of each type of water used is 17 L by using a comparison of soaking times of 1 hour, 3 hours, and 24 hours in gallon water dispenser number 1 and number 2. Swamp water was used during the trial stage because it has a darker colour (brownish-black). The trial was carried out in 5 repetitions. Each repetition used 9 L of water. The water was filled in the first-gallon water container for 2 hours, then another badge was set aside in the second gallon for 1 hour. After four attempts, clear water was obtained, while in the 5th attempt, the water obtained was slightly turbid and contained high calcium. The test results for the pH meter of the swamp water was 6.7, and TDS (Total Dissolve Solid) result was 255 mg/L which was classified as very good.